2019
DOI: 10.1002/bdr2.1505
|View full text |Cite
|
Sign up to set email alerts
|

A case–control analysis of maternal diet and risk of neural tube defects in Bangladesh

Abstract: Objectives: Mothers need a nutrient-rich diet for healthy neural tube development. Neural tube defect risk can be reduced through fortifying grain products with folic acid and taking folic acid supplements. Fortification is not required in Bangladesh. Maternal supplement use rates are low, similar to other countries.This study evaluates maternal dietary intake during pregnancy to identify possible interventions. Methods: A food frequency questionnaire (FFQ) assessed maternal diet. The primary aim compared diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
0
13
0
3
Order By: Relevance
“…A exemplo disso, o Brasil, em que a prevalência geral de defeitos do tubo neural caiu de 0,79 acometidos a cada 1000 nascidos no período de pré-fortificação para 0,55 a cada 1000 nascidos no período de pós-fortificação. (De la Fournière et al, 2020;Obrycki et al, 2019;Blencowe et al, 2018;Santos et al, 2016;Bannink et al, 2015;Idowu et al, 2008;Mitchell, 2005;Jooma, 2004).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A exemplo disso, o Brasil, em que a prevalência geral de defeitos do tubo neural caiu de 0,79 acometidos a cada 1000 nascidos no período de pré-fortificação para 0,55 a cada 1000 nascidos no período de pós-fortificação. (De la Fournière et al, 2020;Obrycki et al, 2019;Blencowe et al, 2018;Santos et al, 2016;Bannink et al, 2015;Idowu et al, 2008;Mitchell, 2005;Jooma, 2004).…”
Section: Discussionunclassified
“…A alimentação rica em vitaminas e minerais variados é de extrema importância como fator de proteção para uma série de doenças, principalmente aquelas do sistema nervoso central. (Obrycki et al, 2019). Em consonância a essa informação, o estudo Deb et al (2018) descobriu que na Índia, país de base vegetariana, as taxas de defeitos no tubo neural são 1,6 vezes mais altas que no restante do mundo e que esse estilo de alimentação sem carnes representa mais um fator de risco para a ocorrência de meningomielocele.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Research conducted globally has provided strong evidence linking maternal arsenic exposure with an increased risk for NTD affected offspring. Studies conducted in Bangladesh have been particularly informative, given that Bangladesh has one of the highest prevalence rates of NTDs in the world ( Mazumdar, 2017 ), and the large segments of the Bangladeshi population suffers from excessive exposure to arsenic from drinking well water ( Mazumdar et al, 2015 ; Kancherla et al, 2017 ; Obrycki et al, 2019 ). As arsenic is methylated during its biotransformation, there is a concern that in populations that are highly exposed to arsenic, folate status would be an important confounding variable with respect to NTD prevalence.…”
Section: Clinical Findings and Epidemiologymentioning
confidence: 99%
“…Additionally, a study conducted by Obrycki et al in 2019 [7] found that mothers in Bangladesh were consuming less than half the RDA for folate. Combined with Bangladesh's lack of formal legislation for folic acid fortification in foods and high prevalence of malnutrition [8], the apparent differences in folate intake in this study may have played a clinically significant role.…”
mentioning
confidence: 99%